Optimizing Library Services through Mediated Communication Exploring Human-Machine Interaction in the Digital Age (Universitas Terbuka, 2024)
Chatbots have become an integral part of our digital lives, presenting new ways of interacting with machines and information. Communication is mediated through chatbots, where humans and machines exchange information and ideas through chats, opening up new communication opportunities and challenges. The library, as the main unit of a university, has the primary task of providing services for librarians to feel comfortable in finding and obtaining the necessary references. Based on the concepts of mediated communication, digital libraries, and chatbots, we will also use literary analysis, focused group discussions, and narrative analysis. The library must be able to adapt and adapt to technological developments, in providing its services to librarians. This article provides an overview of the form of communication media as a means of facilitating librarians in obtaining information quickly and accurately. A library is a service unit, so the input from a librarian is the ammunition for the existence of a library. Before getting a service, of course, sufficient information is needed, accurate and quick so that librarians can more easily browse the references in the library, especially in today's digital age, where we have to revolutionize ourselves to respond to technological changes. From the discussion and analysis of some literature, this article provides an overview of the need for mediated communication patterns in providing more effective and efficient services, in this case through Chatbot.